Inventive thinking among rural students: a preliminary research - Bambang Azhari, Harizah Aliah; Mazlan, Nurul Hijja; Zeki, Mohd Zaidi; Najib, Nuha Khadijah; Riyan Hidayat, .; Talib, Nor Zanariah (Penerbit Universiti Islam Selangor, 2024)
Inventive thinking is identified as one of the most significant skills for addressing 21st-century challenges. This skill serves as a catalyst for the Malaysia government's efforts to nurture innovative and creative culture responding to the digital disruption demands. This effort is aimed to narrow down the inequality gaps between rural and urban areas by fostering quality education and training for citizen. Therefore, this study aims to determine rural students' level of inventive thinking. This study utilized a survey design with instrument is adapted from the Systematic Inventive Thinking Model. Simple random sampling was employed by selecting thirty rural students from Form Four Science stream in Seremban, Negeri Sembilan. This study is significant for assessing students' ability to think inventively. The findings showed that the rural students' level of inventive thinking was moderately low. Therefore, there is a need to foster rural students' inventiveness within the classroom context. Stakeholders are responsible to monitor, strategize, and implement intervention programs to enhance particularly rural students' inventive thinking.